Pengaruh Aspek Keprilakuan Terhadap Sistem Informasi Akuntansi Pada Kantor Perumda Air Minum Wair Pu’an Kabupaten Sikka - Maria Avelina Mistika Dua Bura; Siktania Maria Dilliana; Paulus Libu Lamawitak (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The research aims to determine the influence of behavioral aspects on the accounting information system at the Wair Pu'an Drinking Water Perumda Office, Sikka Regency. The type of research used is a quantitative approach, the data obtained is primary data, data collection techniques include observation, interviews, documentation, questionnaires and literature study. The data analysis method uses the SPSS version 26 program. The research results show simultaneously that the variables of attitude, motivation, perception and emotion have a significant effect on the accounting information system. Furthermore, partially the attitude, motivation and emotion variables have a significant effect on the accounting information system, while the perception variable has no significant effect on the accounting information system. As much as 59.7 percent of accounting information system variables are explained by independent variables (attitude, motivation, perception and emotion) in the research, the remaining 40.3 percent is explained by other variables that are not in this research.